“Et relegendo cognovimus”: scribes and written word in local contexts in León. Tenth and eleventh centuries - Godoy, Analía (En la España Medieval, 2018)
During the tenth and eleventh centuries, the number of charters and written documents was notably increased in the northern Iberian Peninsula. Documents production and transmission were not restricted to the royal and upper ecclesiastical sphere. The present study sets out a wider analysis of the circulation of the written word both in the form of liturgical books and legal codices at local communities or charters drawn up by non monastic scribes. This work proposes the existence of an unspecific group of rural priests who, despite being part of the peasant society, had some legal and religious knowledge and could record certain charters, which allowed them to hold a distinguished position between the rural communities and thus become mediators in the relationship between aristocracy and peasants.